(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
In Rasashastra all the formulations are primarily divided into four groups viz., Kharaliya rasayana, Parpati rasayana, Kupipakwa Rasyana and Pottali Rasayana. Pottali kalpana, one of the above-mentioned rasa rasayanas, has many qualifications, including minimal product waste, minimal drug dosage, rapid efficacy, and high potency in comparison to other Rasayogas. Tridhatu Garbha Pottali is a Sagandha, Sagni, Gandhakajarita, Kajjali bandha Pottali Kalpana containing Swarna, Naga Bhasma, Vanga Bhasma, Yashada Bhasma, Parada and Gandhaka processed in appropriate temperature. As described by Pandit Hariprapannaji in Rasa Yoga Sagar, this is a rare, one of a kind, potent, cost-effective, novel molecule with highly prospective therapeutic applications, particularly in Prameha, Putimeha, Pradararoga, and Shukradosha.